Extraarticular pigmented villonodular synovitis of the hip - Tatari, Hasan; Baran, Önder; Havıtçıoğlu, Hasan; Manisalı, Metin; Koyuncuoğlu, Meral; Özaksoy, Dinç (The Turkish Journal of Pediatrics, 2004)
Pigmented villonodular synovitis of any joint in the extraarticular region is very rare. Its clinical and radiological differential diagnosis is difficult due to exhibiting findings of any soft tissue tumor. Here we report an extrarticular pigmented villonodular synovitis case of the hip of a five-year-old boy, with its radiological and histopathological aspects. The mass was completely extraarticular and was identified histologically and radiologically as pigmented villonodular synovitis. Six months after marginal excision, the lesion recurred. The physicians can face such cases of pigmented villonodular synovitis presenting with unusual extraarticular location, and the preferred excision should be wide to avoid possible recurrences.